Corticosteroids alter alveolar macrophage control of Lichtheimia corymbifera spores in an ex vivo mouse model. (28th December 2020) - Brunet, Kévin; Arrivé, François; Martellosio, Jean-Philippe; Lamarche, Isabelle; Marchand, Sandrine; Rammaert, Blandine
Abstract: Alveolar macrophages (AM) are the first-line lung defense against Mucorales in pulmonary mucormycosis. Since corticosteroid use is a known risk factor for mucormycosis, the aim of this study was to describe the role of corticosteroids on AM capacities to control Lichtheimia corymbifera spore growth using a new ex vivo model. An in vivo mouse model was developed to determine the acetate cortisone dose able to trigger pulmonary invasive infection. Then, in the ex vivo model, male BALB/c mice were pretreated with the corticosteroid regimen triggering invasive infection, before AM collection through bronchoalveolar lavage. AMs from corticosteroid-treated mice and untreated control AMs were then exposed to L. corymbifera spores in vitro (ratio 1:5). AM control of fungal growth, adherence/phagocytosis, and oxidative burst were assessed using optical densities by spectrophotometer, flow cytometry, and 2', 7'-dichlorofluoresceine diacetate fluorescence, respectively. Cortisone acetate at 500 mg/kg, at D-3 and at D0, led to pulmonary invasive infection at D3. Co-incubated spores and AMs from corticosteroid-treated mice had significantly higher absorbance (fungal growth) than co-incubated spores and control AMs, at 24 h ( P  = .025), 36 h ( P  = .004), and 48 h ( P  = .001). Colocalization of spores with AMs from corticosteroid-treated mice was significantly lower than for control AMs (7.6 ± 1.9% vs 22.3 ± 5.8%; P  = .003), reflecting spore adherence and phagocytosis inhibition. Finally, oxidative burst was significantly increased when control AMs were incubated with spores ( P  = 0.029), while corticosteroids hampered oxidative burst from treated AMs ( P  = 0.321). Corticosteroids enhanced fungal growth of L. corymbifera through AM phagocytosis inhibition and burst oxidative decrease in our ex vivo model. Lay Summary: The aim of this study was to describe the impact of corticosteroids on alveolar macrophage (AM) capacities to control Mucorales growth in a new murine ex vivo model. Corticosteroids enhanced fungal growth of L. corymbifera through AM phagocytosis inhibition and burst oxidative decrease.